THE EFFECT OF SOFT SKILLS AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT HANNI PEBAYURAN CLINIC - Novia Dewi Kusmarini; Zulkifli Rangkuti; Nurwulan Kusumadevi (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to analyze the effect of soft skills and work discipline on the performance of employees at Hanni Pebayuran Clinic. The study is grounded in the important role of soft skills and work discipline in shaping employee performance. This research employed a quantitative method with descriptive and verificative approaches. Data were collected through questionnaires distributed to 30 employees of Hanni Pebayuran Clinic and were subsequently analyzed using multiple linear regression. The results indicate that both soft skills and work discipline have a positive and significant effect, both partially and simultaneously, on the performance of employees at Hanni Pebayuran Clinic. This study concludes that improving soft skills and work discipline is essential to optimizing employee performance at Hanni Pebayuran Clinic.